Coconut honey: The effect of storage temperature on some of its physico-chemical properties - Ghazali, H.M.; Sin, M.K. (1986)
The effects of storage at room temperature (28 ± 2°C) and at 50°±2° on some of the physico-chemical properties of coconut (Cocos nucifera) honey were studied. The honey used was collected from hives of Apis cerana in Johore, Malaysia, and extracted by filtering and squeezing through 2 layers of cheese-cloth under conditions as aseptic as possible. Changes in moisture content, water activity (Aw), pH, acid content and total nitrogen content were comparatively small at either temperature. Storage at 50° affected colour adversely. Darkening progressed more quickly at 50° and at the end of 18 weeks the degree of darkening was about six times as great as in honey stored at 28°. Contents of glucose, fructose and sucrose decreased with time at both temperatures, rates of decrease being similar at the 2 temperatures for hexoses but greater at 50° for sucrose. Fructose content declined more than glucose. © 1986 International Bee Research Association.